Evaluasi Sifat Mekanik Sambungan Saw Material BS 1501 223 490B Melalui Uji Destruktif - Hendra Susilo; Putra Pratama; Suardi; Fadlah K. Sinurat (CV. Hawari, 2025)
his study aims to evaluate the mechanical properties of welded joints produced using the Submerged Arc Welding (SAW) method on BS 1501 223 490B steel material. The evaluation was carried out through destructive testing, including tensile test, bend test, and Charpy impact test. The tensile test revealed a maximum tensile strength of 584.39 N/mm² on the All Weld specimen, with an elongation of 26.23%. In the Transverse test, fracture occurred in the base metal, indicating that the weld joint had superior quality compared to the parent material. The bend test on both Face Bend and Root Bend specimens showed visually